Perceived Risk, Market Risk, and Accounting Determined Risk Measures - Farrelly, Gail E.; Ferris, Kenneth R.; Reichenstein, William R. (The Accounting Review, 1985)
[This paper investigates the issue of whether financial reports appear to convey, at least in an implicit fashion, information on risk. The paper extends previous analyses by using the risk perceptions of a representative group of financial analysts as surrogates for ex ante risk. Our findings indicate that the seven accounting measures of risk used in the study "explain" approximately 79 percent of the variation in the average risk perceptions of the financial analysts surveyed. Tests were also performed which support the use of the analysts' risk perception measure as a proxy for a stock's "true" market risk.]